DETERMINANTS OF ECONOMIC GROWTH IN NIGERIA - Ighodaro, Clement A. (University of Nigeria Journal of Political Economy, 2021)
Today, Nigeria’s greatest desire is economic transformation and sustained increased economic growth and development. Policy makers need more empirical inputs to carry out rational economic decisions as well as on specific areas that most policies and strategies should be geared towards. The paper considers the determinants of economic growth in Nigeria using data for 1981 to 2010 and the ARDL estimation technique. Foreign aid influences economic growth in a cubic manner with increasing foreign aid increasing economic growth until a point is reached beyond which growth would actually fall. The coefficient of ECM implies that more than 40% of the deviations of the previous year disequilibrium is corrected in the present year. The result further shows that short run deviations of economic growth are mainly influenced by labour force. It is recommended that foreign aid from our development partners should be judiciously used, particularly, for capital projects rather than for recurrent or immediate consumptions expenditure.